PERJANJIAN JUAL BELI BERBASIS DIGITAL DITINJAU DARI ASPEK HUKUM PERDATA: DIGITAL-BASED PURCHASE AGREEMENT FROM CIVIL LAW ASPECTS - Fadlan, Fadlan (Badan Penerbit STIEPARI Press, 2022)
The purpose of this study is to find out how the legal review of the sale and purchase agreement through e-commerce and to find out the time and validity of the agreement in the electronic sale and purchase agreement. The data collection method used is primary legal materials, namely laws and court decisions. Secondary legal materials are various literatures, expert opinions, legal dictionaries. Non-legal materials such as the Big Indonesian Dictionary and economic books. The results of the research conducted that the validity of online buying and selling agreements by parties with different legal systems, remains valid. This can be seen even though the different legal systems of the agreement occur because of a prior agreement between the parties, where when they want to enter into an e-commerce contract the parties can determine the choice of law and the choice of which forum is the basis for implementing e-commerce as well as being a second agreement. parties in the event of a dispute in the future. If a choice of law is not made, then to determine the applicable law, the principle/theory (the most characteristic) in Civil Law must be used.